2019
DOI: 10.14505//jemt.10.1(33).20
|View full text |Cite
|
Sign up to set email alerts
|

Logistics System of Waste Management at the Mining Enterprises

Abstract: The article considers the solutions related to the formation and use of production and consumption wastes at the enterprises of the mineral resources complex. Particular attention is paid to production waste in the form of solid mineral waste (man-made mineral deposits), which, on the one hand, represents a secondary mineral resource base, on the other hand - has a significant negative impact on various elements of the environment. The research aim is to form a logistics system of waste management at the enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…& District Mohmand Khyber Pakhtunkhwa Pakistan (Mochalova et al, 2019). Exposure of heavy metals with various anthropogenic substances can stop the growing bacteria in the area where important bacteria are lost which can help ride a nutrient bike without a negative impact on the ecosystem (Singh and Kamal, 2017).…”
Section: Impacts Of Mining On Local Fauna Of Wildlife In District Mardanmentioning
confidence: 99%
“…& District Mohmand Khyber Pakhtunkhwa Pakistan (Mochalova et al, 2019). Exposure of heavy metals with various anthropogenic substances can stop the growing bacteria in the area where important bacteria are lost which can help ride a nutrient bike without a negative impact on the ecosystem (Singh and Kamal, 2017).…”
Section: Impacts Of Mining On Local Fauna Of Wildlife In District Mardanmentioning
confidence: 99%
“…Organization of mining museums, cultural monuments, expositions at the site of closed mining workshops, mines Source: compiled by the authors based on [10,11] and own observations When studying the logistics methods of waste management in relation to the mineral resources sector, the authors of the article found out the fact of their usefulness and, accordingly, received prove of the possibility of their use as secondary raw materials. At the mining enterprise, in addition to the main production flows, it is advisable to allocate material flows associated with subsurface waste [12,13].…”
Section: Redesignmentioning
confidence: 99%